Study on the Effect of Amygdales on Mechanical Characteristics of Basalt Using the Combined Finite-Discrete Element Method - Shirui Zhang; Shili Qiu; Ping Li; Yongyuan Kou; Pengfei Kou (Advances in Materials Science and Engineering)
Amygdaloidal basalt, as a heterogeneous rock, is widely exposed at Baihetan hydropower station, China. The geometric effect of amygdales needs further studies and quantifying the shape, orientation, and statistical distribution of amygdales plays an important role in the laboratory and numerical experiments. Therefore, digital image processing (DIP) was first utilized to build a heterogeneous model (HM) to calibrate against the laboratory test results. Then, the heterogeneous models (HMs) with prescribed geometric features were generated by the inverse Monte-Carlo (IMC) algorithm. The uniaxial compression experiments based on HMs were conducted to study the mechanism of the crack initiation and propagation in the amygdaloidal basalt. The tensile fractures were mainly occurred in the matrix, and the shear fractures were mainly occurred in the amygdales. With the increase in the elliptic coefficient of amygdales, the uniaxial compressive strength (UCS) showed a linear growth trend. With the increase in the orientation of amygdales, the UCS exhibited a “V-shaped” distribution characteristic. This paper provides a numerical method for studying the mechanical properties of rocks with flaws.